MODIFICATION OF STARCH BY ESTERIFICATION FOR STARCH INCLUSION FORMATION COMPLEX WITH SODIUM DODECYL SULPHATE - RAHMI FATHIDA ( NIM : 10512045), DAHLIA
A modified starch is a starch that having its hydroxy groups converted into another functional groups through chemical reactions. This treatment may include the use of heat, acid, alkali, oxidizing agent, or other chemicals that will produce new functional groups which will change physical and chemical properties of starch. In this research, starch modification was conducted using acetic acid, acetyl chloride, acetyl acetone and acetic anhydride. The FTIR results of starch modified showed several significant peaks: –OH peak at a wave number of 3000 – 3500 cm-1, –CH (alkanes) at a wave number of around 2900 cm-1, –COO (ester) at a wave number of around 1600 – 1700 cm-1, and –CO peak at a wave number of 1000 cm-1. The peak appearance of ester peaks showed that –OH groups in starch were subtitued by –COOR groups. Variations of the amounts of added reagents was 2.5 mL, 6.25 mL, 10 mL, 12.5 mL. the use these variations resulted in different degrees of subtitution. The higher amounts of the reagent, the greater degree of subtitution of the hydroxyl groups. Using the same amount of reagent, starch modification using acetic anhydride resulted in higher degree of subtitution. The resulting modified starch was complexed with sodium dodecyl sulphate (SDS). The FTIR spectrum of starch – SDS complex showed a shift in vibration peak of S=O which was originally located at wave number 1200 cm-1 to 1500 cm-1 which indicates that there are interactions between starch and SDS. Vibration for the modified starch – SDS complex FTIR spectra indicated a shift in the vibration peak of S=O at wave number of 1300 cm-1.